Reducing Mental Health Stigma: The Relationship between Knowledge and Attitude Change - Simmons, Laura; Jones, Tim; Bradley, Eleanor (European Journal of Mental Health, 2017)
The Relationship between Knowledge and Attitude Change: The impact of how knowledge can effect attitude change is important in order to understand the consequences for stigma. The relationship between increasing subject knowledge of mental health and attitude change was explored. The sample comprised 39 students (18 male and 21 female)from a university in the West Midlands. Participants’ level of knowledge and stigma were recorded through pre- and post-tests using the Mental Health Knowledge Schedule (MAKS), Community Attitudes toward the Mentally Ill (CAMI) and the Opinions about Mental Illness (OMI) scale. Information about mental illness was provided between conditions followed by a distractor task. Responses were calculated and combined to give an overall score. A sign test with continuity correction was used to see whether there was a difference in attitudes. The pre- and post-test conditions were scored. Results demonstrate a statistically significant median decrease in stigma in the post-test condition (p = 0.03). Therefore, this research provides support for the success of providing knowledge and information about mental illness in order to reduce stigma.